FEATURES OF PSYCHOEMOTIONAL STATE, NEUROTRANSMITTER AND HORMONAL STATUS IN PATIENTS WITH ARTERIAL HYPERTENSION - Гринів, О. І.; Глушко, Л. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Psycho-emotional and vegetative disorders in patients with arterial hypertension are responsible, regardless of the presence of comorbidity, the formation of unfavorable prognosis of the disease as in the stabilization phase, and at the stage of progression. Regulatory imbalance of neurotransmitter systems in patients with arterial hypertension is often manifested by anxiety, motor tension, autonomic hyperactivity and activation hotelami-pituitary-adrenal system. The aim of this work was to study the relationship of mental and emotional disorders with neiromediatorne and hormonal changes in patients with arterial hypertension. Methods: the present study included 145 patients with hypertension stage I and II, aged 29 to 53 years (mean age 46,75 ± 0.56 years). Of them group 1 comprised 36 patients with hypertension and stage and group II – 109 patients with hypertension stage II. The control group included 20 practically healthy people without hypertension. Results: in individuals of arterial hypertension And, especially, of the second class noted significantly high levels of reactive and situational anxiety clinically significant depression and alexicon. The group surveyed with AH of II degree was characterized by a significant change in the ratio norepinephrine/epinephrine, elevated levels of cortisol and serotonin. Correlation of biochemical parameters with psychological factors. Conclusions: psycho-emotional imbalance triggered by the stress response accompanied by metabolic changes (neurotransmitter mechanisms). The study of the psychosomatic continuum is important for uncovering the mechanisms of influence of stress and psycho-emotional stress on the development of the course of diseases, development of integrated approach to the prevention and complex treatment of arterial hypertension.